In Situ/Operando Characterization Techniques: The Guiding Tool for the Development of Li–CO2 Battery. Issue 12 (4th November 2022) - Chourasia, Ankit K.; Pathak, Anil D.; Bongu, Chandrasekhar; Manikandan, K.; Praneeth, Sai; Naik, Keerti M.; Sharma, Chandra S.
Abstract: In recent times, the Li‐CO2 battery has gained significant importance arising from its higher gravimetric energy density (1876 Wh kg ‐1 ) compared to the conventional Li‐ion batteries. Also, its ability to utilize the greenhouse gas CO2 to operate an energy storage system and the prospective utilization on extraterrestrial planets such as Mars motivate to practicalize it. However, it suffers from numerous challenges such as (i) the reluctant CO2 reduction/evolution; (ii) solid/liquid/gas interface blockage arising from the deposition of Li2 CO3 discharge product on the cathode; (iii) high overpotential to decompose the stable discharge product Li2 CO3 ; and (iv) instability of the electrolytes. Numerous efforts have been undertaken to tackle these challenges by developing catalysts, improving the stability of electrolytes, protecting the anode, etc. Despite these efforts, due to the lack of a decisive confirmation of the reaction mechanisms of the discharging/charging reactions occurring in the system, the progress of the Li–CO2 battery system has been slow. In situ characterization techniques help overcome ex‐situ techniques' limitations by monitoring the processes with the progress of a reaction. The current review focuses on bridging the gap in the understanding of the Li–CO2 batteries by exploring the various in situ/operando characterization techniques that have been employed. Abstract : The different in situ and ex situ techniques that are utilized to explore the Li–CO2 battery chemistry are enlisted. It can guide student, researcher, industry, and experts to venture their research into the Li–CO2 battery domain through the combination of the different in situ and ex situ characterization techniques.